2019
DOI: 10.1115/1.4042466
|View full text |Cite
|
Sign up to set email alerts
|

Large and Infinite Mass–Spring–Damper Networks

Abstract: This paper introduces mechanical networks as a tool for modeling complex unidirectional vibrations. Networks of this type have branches containing massless linear springs and dampers, with masses at the nodes. Tree and ladder configurations are examples demonstrating that the overall dynamics of infinite systems can be represented using implicitly defined integro-differential operators. Results from the proposed models compare well to numerical results from finite systems, so this approach may have advantages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…To compute the time-response of the multivalued transfer function in (5), we consider the following definition of the inverse Laplace transform:…”
Section: Appendix a Examplementioning
confidence: 99%
See 1 more Smart Citation
“…To compute the time-response of the multivalued transfer function in (5), we consider the following definition of the inverse Laplace transform:…”
Section: Appendix a Examplementioning
confidence: 99%
“…[4] uses fractances in a lumped model of the cardiovascular system, leading to the description of different types of heart anomalous behaviors. In [3,5,6], ISs are introduced to describe robotic formations in the form of tree-like networks and ladder-like networks. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, by taking the real and imaginary part of Equation 12and, solving with respect to k p and k leads to Equations (10) and (11), respectively. □ Proposition 3 (CRB, = 0).…”
Section: Complex Root Boundariesmentioning
confidence: 99%
“…In addition, in the work of Podlubny [28], it has been shown that PI 𝜆 D 𝜇 controllers provide better results when being applied to fractional-order systems. Therefore, because ISs are a type of fractional-order systems [2,10], fractional-order controllers are the most suitable option to control ISs. In general, fractional-order systems' stability and fractional-order PID controllers's design have been already studied for different applications, for some examples, see refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation